Peranan Perpustakaan Sekolah Dalam Meningkatkan Minat Baca Siswa SDIT Iqra' Kota Solok - Pri Utami; Bakhtaruddin Nst. (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study was to describe about schools in improving student reading Solok City (1) the role of libraries SDIT Iqra' Solok City in improving students reading interest, (2) the books in the library SDIT Iqra' Solok City can serve as supporting the learning process of students class, (3) constraints encountered in developing an interest in reading in the Library SDIT Iqra' Solok City. Data were collected through observation and interviews with librarians in SDIT Iqra' Solok City data required for the necessary methods and techniques of data collection fact that evidence can be obtained. The method used is descriptive analysis. By analyzing the data, it is concluded - following. First, the role of libraries SDIT Iqra' include: improvement of service the library, the school library should provide a collection. Second, the books in the library SDIT Iqra' Solok City can serve as supporting students' learning process, students are introduced directly by the user according to the subject being taught, and the teachers presenting latest book to every student so that students can be interested read books the library school. Third, problems encountered in the development of reading interest in the Library SDIT Iqra'Solok City are: (1) limited collection library, (2) that has not been ideal library space, (3) professionals who have not been fixed. Keywords: library, reading interest